PENGARUH KUALITAS PELAYANAN BELLBOY TERHADAP KEPUASAN TAMU DI HOTEL GRAND ROCKY BUKITTINGGI - Pratama, Randy; Waryono, Waryono; Abrian, Youmil (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2017)
Purpose of this are: (1) Describing bellboy service quality, (2) Describingguest statisfaction and (3) analize an affecttion of bellboy service towards gueststatisfaction in Grand Rocky Hotel Bukittinggi. Type of this research were allguest in Grand Rocky Hotel Bukittinggi. According to sampling purposive, 100guest has been collected as sample. Data was collected by using the questionnairewhich has been tested the validity and reability. Then, data were analyzeddescriptively and correlation with the assistance of a computer program 16.00 spssversion. The result showed taht: (1) bellboy service quality are in low category(57%), (2) guest statisfaction are in low (86%) and (3) there is significant affectbetween the quality of service to the guest statisfaction in Grand Rocky HotelBukittinggi of (34%) while (66%) influenced by the other factors.Keywords: service quality, guest statisfaction, bellboy1Prodi